Interleukin-6 and procalcitonin in children with sepsis and septic shock - Fioretto, José Roberto [UNESP]; Martin, Joelma Gonçalves [UNESP]; Kurokawa, Cilmery Suemi [UNESP]; Carpi, Mario Ferreira [UNESP]; Bonatto, Rossano César [UNESP]; Ricchetti, Sandra M. Q. [UNESP]; de Moraes, Marcos A. [UNESP]; Padovani, Carlos Roberto [UNESP] (Academic Press Ltd Elsevier B.V. Ltd, 2008)
Objectives. To examine the behavior of interleukin-6 (IL-6) and procalcitonin (PCT) and verify whether they can be used to differentiate children with septic conditions. Methods. Septic children aged between 28 days and 14 years, prospectively enrolled from 01/2004 to 12/2005, were divided into sepsis (SG; n = 47) and septic shock (SSG; n = 43) groups. IL-6 and PCT were measured at admission (TO) and 12 h later (T12h). PCT results were classed as: 0.5 ng/mL = sepsis unlikely; >= 0.5 to < 2 = sepsis possible; >= 2 to < 10 = systemic inflammation: >= 10 = septic shock. Results. Ninety children were included. At TO, there was a higher frequency of SSG with higher PCT compared with SG [SSG: 30 (69.7%) > SG: 14 (29.8%): p < 0.051. Similar results were observed at T12h. PRISM was significantly higher for SSG patients with higher PCT than SG patients. At TO, IL-6 levels were higher in SSG [SSG: 213.10 (10.85-396.70) > SG: 63.21 (0.86-409.82); p = 0.001], but not statistically different at T12h. IL-6 levels positively correlated with PRISM score in SSG patients at admission (p = 0.001; r = 0.86). Conclusion. PCT and IL-6 appear to be helpful in early assessment of pediatric sepsis, are of diagnostic value at admission, and are related to disease severity. (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: procalcitonin; interleukin-6; sepsis; septic shock; children